Enhancement of solar cell efficiency using perovskite dyes deposited via a two-step process1. Issue 42 (10th May 2015) - Duong, Thanh-Tung; Kim, Yun-Jeong; Eom, Ji-Ho; Choi, Jin-Seok; Le, Anh-Tuan; Yoon, Soon-Gil
<x xml:space="preserve">Abstract</x> This study examined the effect of different thick-compact-TiO2 blocking layers (c-TiO2) and mesoporous-TiO2 layers (m-TiO2) on the efficiency of perovskite cells.